Effects of Physical Activity on Vasomotor Symptoms: Examination Using Objective and Subjective Measures - Elavsky, Steriani (2012)
OBJECTIVE: Physical activity (PA) is essential for successful aging and for the prevention and management of common chronic diseases. The empirical support for the beneficial effects of PA on vasomotor symptoms has however been mixed. The purpose of this study was to assess the effects of acute aerobic exercise and daily PA on menopausal vasomotor symptoms. METHODS: Community-dwelling midlife women (N = 121; age range 40–60 years) not on hormone therapy were recruited for a 15-day daily diary study. Women completed psychological, cardiorespiratory fitness, body composition, and hormonal status screening, followed by a 15-day prospective assessment in a “real-life” setting using a personal digital assistant device. Participants also completed a 30 minute moderate-intensity aerobic exercise bout on a treadmill between days 5–8. Daily PA was assessed objectively through accelerometry and all symptomatic women (n = 92) completed two 24-hour Biolog sternal skin conductance recordings of hot flashes (HFs), one at baseline and one immediately following treadmill exercise. RESULTS: Both total objective (p = .054) and total subjective (p < .05) HFs decreased following the acute exercise bout. At the between-person level, daily PA was not associated with self-reported HFs. However, at the within-person level, performing more moderate physical activity than usual was associated with more self-reported HFs in women with lower fitness levels. CONCLUSIONS: Moderate aerobic exercise decreases objective and subjective HFs 24 hours following exercise, however, in women with lower fitness levels, more daily moderate PA leads to more self-reported symptoms.